Potentials of Antitussive Traditional Persian Functional Foods for COVID-19 Therapy† - Mosleh, Ghazaleh; Badr, Parmis; Zaeri, Meysam; Mohagheghzadeh, Abdolali (Frontiers in Pharmacology, 2021)
The coronavirus disease 2019 is a worldwide pandemic resulted in a severe acute respiratory syndrome. Remdesivir is its only FDA-approved drug for hospitalized patients≥12 years of age. It reveals the necessity of finding new therapeutic strategies. Functional foods (FFs) could have co-therapeutic and protective effects against COVID-19 infection. Traditional Persian medicine (TPM) as one of the safest and most popular medicine for hundreds of years has recommended potential FF candidates to manage such global pandemic. For revealing potential of TPM for antitussive FFs, the traditional Persian pharmacopoeia "Qarabadin-e-Salehi" was searched using the keyword of "Soaal" and "Sorfeh". Also, recent studies were collected from MEDLINE, PubMed Central, Google Scholar, and Science Direct, with the search terms of ingredient names combined with "antitussive", "cough", "antioxidant", "anti-inflammation", "antiviral", and "COVID-19". Then their potential mechanism of action in SARS‐CoV‐2 infection were discussed. Twelve TPM FFs were found which include Laooqs, Morabbas, a Saviq, a soup, and a syrup. They are combinations of 2-7 ingredients. Natural compounds of mentioned formulations have main pharmacological mechanisms including antioxidant, anti-inflammatory, anti-alveolar edema, antiviral, anti-asthmatic, antispasmodic, analgesic, antipyretic, anti-tyrosine kinase, demulcent, prebiotic, immunomodulatory, lung protective, Nrf2 pathway controlling, and in silico binding affinities against COVID-19. FFs have possible therapeutic effects against COVID-19 virus. FFs might have positive psychological effects along with their pharmacological effects and nutritional virtues. FFs are cost-benefit, easily accessible, and safe options for both treatment and prevention of the disease. They could also manage persistent respiratory discomforts after the recovery of COVID-19.